Estimating Drivers and Pathways for Hydroelectric Reservoir Methane Emissions Using a New Mechanistic Model. Issue 8 (24th August 2022) - Delwiche, Kyle B.; Harrison, John A.; Maasakkers, Joannes D.; Sulprizio, Melissa P.; Worden, John; Jacob, Daniel J.; Sunderland, Elsie M.
Abstract: Hydroelectric reservoirs can emit significant quantities of methane, particularly through degassing at turbine outlets. Improved understanding of processes affecting hydroelectric reservoir CH4 emissions is thus important as the world economy transitions to renewable forms of energy production. Here we develop and evaluate a new mechanistic model of CH4 emissions: ResME ([Res ]ervoir [M ]e thane [E ]missions), which estimates carbon inputs and methanogenesis to predict CH4 release via ebullition and diffusion, plant emissions, and downstream emissions. ResME results demonstrate that the relative importance of allochthonous and autochthonous carbon input to methane emissions varies by latitude, with allochthonous carbon contributions typically being higher in tropical reservoirs. Results also demonstrate that total reservoir emissions are highly dependent on turbine intake depths, which are not typically reported. Potential maximum degassing emissions from existing hydroelectric reservoirs are estimated as 11 ± 4 Tg C/yr, if all reservoirs had deep turbine intakes and stratified for 5 months per year. In comparison, the estimated diffusive, ebullitive, and plant CH4 emissions are estimated to be 2.8 ± 0.2 Tg C/yr (where the true uncertainty is much higher than the model standard error). Future work should focus on improving estimates of reservoir carbon inputs and decomposition rates, as well as surveying turbine intake depths. Satellite measurements from missions such as TROPOMI may also help constrain hydropower methane emissions. Plain Language Summary: Methane is an important greenhouse gas that is naturally produced in lake and reservoir sediment, among other sources. Hydroelectric power reservoirs produce renewable energy, yet also emit methane at their surfaces, and from turbines and downstream reaches. To better understand drivers and pathways of methane emissions, we have developed a new mechanistic model for methane emissions as a function of carbon inputs, chemical decomposition, and physical processes. Results also show that downstream methane emissions have the potential to exceed surface emissions if turbines pull from stratified, anoxic waters. Large uncertainties remain in model inputs, and future work should focus on improved understanding of carbon loading to reservoirs, as well as decomposition rates and turbine intake depths. Key Points: Our mechanistic model (Reservoir Methane Emissions) illuminates the main drivers of hydropower methane emissions Emissions from downstream degassing are comparable to surface emissions when turbines are parameterized with deep water intakes We estimate global emissions from hydropower surfaces as 2.8 ± 0.2 Tg C/yr, plus 11 ± 4 Tg C/yr from downstream degassing